“A decisão do passo e o júbilo da travessia” – uma introdução ao Inquérito às Quatro Confidências: Diário III, de Maria Gabriela Llansol - Fagundes, Juliana de Araújo (2019)
This dissertation has as its corpus the book by Maria Gabriela Llansol (1931-2008): Inquérito às Quatro Confidências–Diary III, published in 1996. The work unfolds in central themes, like the reader in Maria Gabriela Llansol and the literary criticism thought from this reading. Among its objectives, it seeks to apprehend the inseparability of the reader-writer pair, as well as to broach the images from Llansol called figures. Llansol writes that what drives the writing of this book is the desire to compose a body for her friend Vergílio Ferreira, which allows her to go through death. To seize such a problem, the question is: how does the reader / writer get updated in the textuality of this diary? To what extent can a meeting between pairs produce writingand bring to the text the experience of affective experiences, an invitation to play with body and thought? How does the crossing of Vergílio 's death relate to the body as a place of reading, the Llansolian “sex of reading”, and to writing as a science ofthe enjoyment of language? The hypothesis that stands out is that the reader/writer structures the textuality that is in progress, and summons the critic to a gesture of reading, leading him to write alongside and with the Llansolian text, so as to be accepted in the textuality. The theoretical-critical grounding is based on Llansolian criticalreader,like: Lucia Castello Branco, João Barrento, Silvina Rodrigues Lopes, Jonas Miguel Pires Samudio; it also draws on conceptions of Roland Barthes, Maurice Blanchot and Gilles Deleuze. Among other considerations, this study shows that in Llansol there is a displacement of poetic voices that spread and mix with her voice via overprinting; that the body reinvents itself with libido by the gesture of reading, thatthe root of the Llansolian diary expands the volume of writing